Recession and Family Firm Performance: An Assessment of Small U.K. Family-Owned Hotels - Chaston, Ian (2012)
The prevailing view in the literature is that small family firms outperform nonfamily businesses. The nature of the former’s management style also means that these businesses are more likely to sustain their performance in a recession. Drucker (1985b) extended the Schumpeterian view that the most important time for entrepreneurial behavior is in periods of environmental turbulence such as during a major economic downturn. A mail survey of small family-owned and nonfamily U.K. hotels was utilized to assess business performance, entrepreneurial orientation, and strategic flexibility. Results indicated that family-owned hotels outperformed nonfamily businesses. Family-owned hotels which enjoyed sales growth during the recession were those which exhibit an entrepreneurial orientation and strategic flexibility. This conclusion was found to apply to both family-owned and nonfamily hotels. The implications of these results are that small family firms seeking to survive in a recession should probably exhibit an entrepreneurial orientation and be strategically flexible.